LEGAL IMPLICATIONS OF THE ADMISSION OF EXCEPTIO NON ADIMPLETI CONTRACTUS ON A COUNTERCLAIM IN A BREACH OF CONTRACT CASE - Sinar Tamba Tua Pandiangan; Rachmi Sulistyarini; Hanif Nur Widhiyanti (CV. RADJA PUBLIKA, 2025)
In Indonesian judicial practice, there is a divergence of opinions among judges regarding the legal consequences/implications of the acceptance of Exceptio non adimpleti contractus on counterclaim. This has prompted the author to research the legal implications of the acceptance of Exceptio non adimpleti contractus on the counterclaim in breach of contract cases. This research utilizes a normative legal research method. If Exceptio non adimpleti contractus is granted, the counter claim may still be considered by the panel of judges to fulfill the principles of simple, swift, and low-cost justice. This approach is considered more efficient and avoids delays also additional costs that would arise if the defendant were required to file a new lawsuit. Moreover, within the framework of progressive legal theory, adjudicating a case while considering the counterclaim, even after Exceptio non adimpleti contractus is granted, can provide real benefits to society by ensuring prompter and more affordable access to justice.